Kreps, David M. Arguing about Tastes: Modeling How Context and Experience Change Economic Preferences - Chakraborty, Anujit (Journal of Economic Literature, 2025)
Anujit Chakraborty of University of California, Davis reviews “Arguing about Tastes: Modeling How Context and Experience Change Economic Preferences” by David M. Kreps. The Econlit abstract of this book begins: “Explores preference formation and evolution, discussing the interaction between intrinsic motivation and extrinsic incentives in both static situations and in more dynamic contexts.”